2015
DOI: 10.1016/j.visres.2015.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual information processing in school-age dyslexics and normal readers via motion-onset visual evoked potentials

Abstract: Standard pattern-reversal visual evoked potentials (VEPs) and motion-onset VEPs (M-VEPs) were tested in 19 dyslexics and 19 normal readers aged 7-13 years in order to evaluate the feasibility of M-VEPs for the objective diagnostics of a visual subtype of dyslexia, in which a dysfunction of the magnocellular subsystem/dorsal stream of the visual pathway is suspected. The set of VEPs consisted of the pattern-reversal VEPs with check sizes of 20', two types of translational motion (with low and high contrast) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Although the etiology of dyslexia is not well understood, the current view supports an impairment of phonological processing (Norton, Beach, & Gabrieli, 2014), as well as sensory deficits (e.g., Kubova et al, 2015;Schulte-K€ orne & Bruder, 2010;Stefanics, Fosker, et al, 2011). Auditory MMN has been extensively used to investigate the development of the auditory and speech systems (Cheour et al, 1998 …”
Section: Developmental Disordersmentioning
confidence: 97%
“…Although the etiology of dyslexia is not well understood, the current view supports an impairment of phonological processing (Norton, Beach, & Gabrieli, 2014), as well as sensory deficits (e.g., Kubova et al, 2015;Schulte-K€ orne & Bruder, 2010;Stefanics, Fosker, et al, 2011). Auditory MMN has been extensively used to investigate the development of the auditory and speech systems (Cheour et al, 1998 …”
Section: Developmental Disordersmentioning
confidence: 97%
“…Other studies have used different electrophysiological techniques, such as fixed spatial frequencies with high temporal frequencies and luminance variation,21,23 low spatial frequency and high temporal frequency stimuli (7.5 Hz),20,23 and, finally, recording of VEPs with the use of moving stimuli at low contrast,79 as well as at low contrast and radial motion full field and radial motion periphery 69. In all cases, they showed a significant increase in latencies and a reduction in the amplitudes of the waveform in dyslexic patients 24…”
Section: Discussionmentioning
confidence: 97%
“…Selective electrofunctional investigation of the M pathway requires the use of electrophysiological methods based on the recording of pattern visual evoked potentials (PVEP) and appropriately modified stimuli with regard to contrast, spatial frequency, temporal frequency, and movement 19–24…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have reported higher, lower, and equal visual-spatial abilities with dyslexia. Some studies have reported the superiority of sight-spatial ability in dyslexic individuals but there were studies that did not recognize such processing between dyslexic and non-A dyslexic individuals [23][24][25][26][27], and even the weakness of this process in dyslexic individuals [28,29]. However, those studies that indicate the potential dysfunctional superiority in the field of visual-spatial ability can be a source of further and a new perspective on research in this field.…”
Section: Introduction Ccording To the Diagnostic And Statisticalmentioning
confidence: 99%